2016
DOI: 10.1097/mpg.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Diarrheal Severity Scores in the MAL‐ED Multisite Community‐Based Cohort Study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Others have also found that the Vesikari severity scoring system may overestimate disease severity to some degree . However, different clinical scoring systems have been found to be equally sensitive with regard to predicting clinical outcomes and the Vesikari score was effective in predicting clinical outcome, measured as the length of stay in our population as well as in a US population .…”
Section: Discussionmentioning
confidence: 47%
“…Others have also found that the Vesikari severity scoring system may overestimate disease severity to some degree . However, different clinical scoring systems have been found to be equally sensitive with regard to predicting clinical outcomes and the Vesikari score was effective in predicting clinical outcome, measured as the length of stay in our population as well as in a US population .…”
Section: Discussionmentioning
confidence: 47%
“…Diarrhea was defined as maternal report of three or more loose stools in a 24-hour period or at least 1 stool with visible blood present [ 12 ], and unique diarrheal episodes were separated by at least 2 days without diarrhea [ 10 ]. Dysentery was defined as diarrhea with visible blood reported by the child’s mother during the identified illness episode, and severe diarrhea as diarrhea samples with a modified Vesikari severity score (MAL-ED score) of ≥ 5 [ 13 , 14 ]. Control samples were non-diarrhea stools (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental exposures, such as toxins, stress, nutrition, and infection during pregnancy have all been linked with behavioral, cognitive and neurodevelopmental impairments in offspring (Lee et al, 2016). Emerging evidence suggests that some of these exposures exert their influence via maternal immune regulation (Calderon-Garciduenas et al, 2009; Wright et al, 2010; Gilman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%